Proteomic analysis of mouse kidney peroxisomes: identification of RP2p as a peroxisomal nudix hydrolase with acyl-CoA diphosphatase activity - Ofman, Rob (Portland Press Ltd., 2005)
Proteomic analysis of mouse kidney peroxisomes resulted in the identification of a novel nudix hydrolase designated RP2p, which is encoded by the D7RP2e gene. RP2p consists of 357 amino acids and contains two conserved domains: a nudix hydrolase domain and a CoA-binding domain. In addition, a PTS (peroxisomal targeting signal) type 1 (Ala-His-Leu) was found at the C-terminus. Analysis of the enzyme characteristics revealed that RP2p is a CoA diphosphatase with activity towards CoA, oxidized CoA and a wide range of CoA esters, including choloyl-CoA and branched-chain fatty-acyl-CoA esters. The enzymatic properties of RP2p indicate that at low substrate concentrations medium and long-chain fatty-acyl-CoA esters are the primary substrates. Enzyme activity was optimal at pH 9 or above, and required the presence of Mg(2+) or Mn(2+) ions. Subcellular fractionation studies revealed that all CoA diphosphatase activity in mouse kidney is restricted to peroxisomes.